Negative electrode active layer, double negative electrode active layer, negative electrode sheet and lithium ion battery

By using carbon-modified lithium metasilicate binder in the negative active layer of the lithium-ion battery, the problem of being unable to meet the strong bonding force, high conductivity and low expansion effects in the prior art is solved, and a lithium-ion battery with high rate performance, low internal resistance and long cycle life is achieved.

CN118867251BActive Publication Date: 2025-03-14ZHEJIANG JINKO ENERGY STORAGE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411332578.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-03-14
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The negative active layer of existing lithium-ion batteries cannot meet the effects of strong bonding force, high conductivity and low dimensional expansion at the same time, affecting the rate performance and cycle life of the battery.

Method used

A carbon-modified lithium metasilicate binder is used to form a carbon-modified lithium metasilicate binder by coating a carbon layer on the surface of the lithium metasilicate core particles, and the adhesive is used in the negative electrode active layer to build a cross-linking network to improve adhesion and conductivity.

Benefits of technology

The internal resistance, adhesion, liquid absorption capacity, expansion ability and ion conduction capacity of the negative electrode sheet are significantly improved, and the rate performance and cycle life of the lithium-ion battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides a negative electrode active layer, a double negative electrode active layer, a negative electrode plate and a lithium ion battery. The negative electrode active layer includes a carbon-modified lithium metasilicate binder, and the content of the carbon-modified lithium metasilicate binder is 2.4% to 3.2% based on the total weight of the negative electrode active layer as 100%. The negative electrode active layer of a lithium ion battery provided by the present invention, which includes carbon-modified lithium metasilicate, can be used as a binder to construct a cross-linked network in the negative electrode active layer, improve the internal resistance, adhesion, liquid absorption capacity, expansion and ion conductivity of the negative electrode plate, and finally obtain a lithium ion battery that can simultaneously take into account high rate performance, low internal resistance and long cycle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium-ion batteries, and in particular to a negative electrode active layer, a double negative electrode active layer, a negative electrode plate and a lithium-ion battery. Background Art

[0002] At present, the cycle life, rate performance, and electrode expansion of lithium-ion batteries have been greatly improved. However, in practical applications, especially in certain extreme environments, there are higher requirements for the cycle life and rate performance of lithium-ion batteries.

[0003] The cycle life of lithium-ion batteries is closely related to the adhesion of the pole piece and the expansion effect of the negative electrode active material. First of all, the cycle life refers to the number of charge and discharge times during which the battery can maintain a certain performance during the charge and discharge process. The longer the cycle life, the better the battery performance. Good pole piece adhesion helps to improve the cycle life of the battery. When the adhesion between the pole piece and the electrode material is strong, the pole piece is not easy to fall off during the charge and discharge process of the battery, thereby reducing the risk of micro-short circuits and thermal runaway inside the battery, and helping to extend the service life of the battery. On the contrary, poor pole piece adhesion may lead to a reduction in the cycle life of the battery. If the adhesion between the pole piece and the electrode material is weak, the pole piece is easy to fall off during the charge and discharge process of the battery, thereby increasing the risk of micro-short circuits and thermal runaway inside the battery, which may cause the battery performance to deteriorate or even damage.

[0004] Also, during the charge and discharge process of lithium-ion batteries, the negative electrode active materials (such as graphite, silicon, etc.) will expand and shrink in volume. This expansion effect may lead to a decrease in the adhesion between the electrode material and the electrode sheet, thereby affecting the cycle life of the battery. At the same time, if the electrode sheet adhesion is poor, the negative electrode active material will easily fall off during the charge and discharge process, which will also lead to a decrease in the battery's electrical performance.

[0005] Based on this, how to provide a negative electrode active layer that has strong adhesion, high conductivity and low dimensional expansion effect, and use it in lithium-ion batteries to improve the battery's rate performance and cycle life is one of the important technical problems that need to be solved in this field. Summary of the invention

[0006] The main purpose of the present invention is to provide a negative electrode active layer, a double negative electrode active layer, a negative electrode plate and a lithium ion battery to solve the problem that the negative electrode active layer of the lithium ion battery in the prior art cannot simultaneously meet the requirements of strong bonding force, high conductivity and low dimensional expansion effect.

[0007] In order to achieve the above objectives, the first aspect of the present invention provides a negative electrode active layer, which includes a carbon-modified lithium metasilicate binder, and the content of the carbon-modified lithium metasilicate binder is 2.4%~3.2% based on the total weight of the negative electrode active layer as 100%.

[0008] Furthermore, the carbon-modified lithium metasilicate binder comprises lithium metasilicate core particles and a carbon layer coated on the surface of the lithium metasilicate core particles; preferably, the D50 of the lithium metasilicate core particles is 10nm~120nm, and the thickness of the carbon layer is 0.1nm~10nm.

[0009] Furthermore, thermogravimetric analysis was performed on the carbon-modified lithium metasilicate binder, and the initial decomposition temperature of the carbon-modified lithium metasilicate binder was 300°C~800°C, and the weight loss percentage was 10%~20%.

[0010] Furthermore, the preparation method of the carbon-modified lithium metasilicate binder includes: step S1, pre-treating the lithium metasilicate powder to obtain lithium metasilicate core particles; step S2, under the protection of an inert gas, mixing the lithium metasilicate powder with a carbon source, and calcining to obtain a carbon-modified lithium metasilicate binder; preferably, the calcination temperature is 400°C to 1000°C, and the time is 0.2h to 4.0h; preferably, the carbon source is selected from one or more of ethanol, ethylene, benzene, hexachlorobenzene and ethylene.

[0011] Furthermore, in step S1, the pretreatment includes: dissolving lithium metasilicate powder in a mixed solvent to obtain a mixed solution; drying the mixed solution at 40°C~42°C to obtain lithium metasilicate core particles; preferably, the mixed solution includes tetraethyl orthosilicate, ethanol and water, and the weight ratio of tetraethyl orthosilicate, ethanol and water is 1:(1.8~2.0):1; more preferably, the weight ratio of lithium metasilicate powder to the mixed solution is 1:(4.0~4.2).

[0012] Furthermore, the negative electrode active layer also includes 95.4% to 96.8% of a first negative electrode active material and 0.8% to 1.4% of a first conductive agent by weight; preferably, the first negative electrode active material is selected from one or more of graphite, silicon and a lithium-containing alloy; and the first conductive agent is selected from one or more of carbon black, carbon nanotubes and graphene.

[0013] The second aspect of the present invention provides a dual negative electrode active layer, comprising a first negative electrode active layer and a second negative electrode active layer stacked in sequence, the first negative electrode active layer is the above-mentioned negative electrode active layer, which includes a carbon-modified lithium metasilicate binder; in terms of weight percentage, the second negative electrode active layer includes 2.2%~3% of a CMC binder and / or an SBR binder, 95.5%~96.7% of a second negative electrode active material, and 0.7%~1.5% of a second conductive agent; the second negative electrode active material is selected from one or more of graphite, silicon, and a lithium-containing alloy; the second conductive agent is selected from one or more of carbon black, carbon nanotubes, and graphene.

[0014] Furthermore, in the dual negative electrode active layer, the thickness ratio of the first negative electrode active layer to the second negative electrode active layer is (0.55-1.55):1; preferably, by weight percentage, the second negative electrode active layer also includes 0.1%-0.3% of a carbon-modified lithium metasilicate binder.

[0015] The third aspect of the present invention provides a negative electrode plate, comprising a negative electrode current collector and a negative electrode active layer arranged on at least one side surface of the negative electrode current collector, wherein the negative electrode active layer is the above-mentioned negative electrode active layer, or the above-mentioned double negative electrode active layer.

[0016] Furthermore, the negative electrode active layer is the above-mentioned double negative electrode active layer, and the first negative electrode active layer in the double negative electrode active layer is arranged in contact with the negative electrode current collector; or the second negative electrode active layer in the double negative electrode active layer is arranged in contact with the negative electrode current collector.

[0017] A fourth aspect of the present invention provides a lithium-ion battery, comprising a positive electrode plate, a negative electrode plate and an electrolyte, wherein the negative electrode plate is the above-mentioned negative electrode plate.

[0018] By applying the technical solution of the present invention, a lithium ion battery negative electrode active layer containing carbon-modified lithium metasilicate is provided, which can be used as a binder to construct a cross-linked network in the negative electrode active layer, improve the internal resistance, adhesion, liquid absorption capacity, expansion and ion conductivity of the negative electrode plate, and finally obtain a lithium ion battery that can take into account high rate performance, low internal resistance and long cycle. DETAILED DESCRIPTION

[0019] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0020] As described in the background art, the negative electrode active layer of lithium ion batteries in the prior art has the problem of not being able to simultaneously meet the requirements of strong bonding force, high conductivity and low dimensional expansion effect. In order to solve the above technical problems, the first aspect of the present invention provides a negative electrode active layer, which includes a carbon-modified lithium metasilicate binder, and the content of the carbon-modified lithium metasilicate binder is 2.4% to 3.2% based on the total weight of the negative electrode active layer as 100%.

[0021] The present invention provides a lithium ion battery negative electrode active layer containing carbon-modified lithium metasilicate, which can be used as a binder to construct a cross-linked network in the negative electrode active layer, improve the internal resistance, bonding force, liquid absorption capacity, expansion and ion conductivity of the negative electrode plate. Specifically, the carbon-modified lithium metasilicate binder provided by the present invention contains hydroxyl groups on its surface, so it can construct a covalent bond and hydrogen bond bonding network in the negative electrode active layer, which helps to alleviate the volume expansion of the negative electrode active layer during use. At the same time, the carbon-modified lithium metasilicate binder itself, as an excellent lithium ion conductor, can be used as a lithium supplement, and cooperates with the negative electrode active material and conductive agent present in the negative electrode active layer to significantly improve the lithium ion diffusion kinetics in the electrode. And, the binder has carbon modification, which can significantly inhibit the damage to the best product caused by poor elasticity of the lithium metasilicate material during the application process, and finally improve the conductivity and long cycle capacity of the negative electrode active layer, and finally obtain a lithium ion battery that can take into account high rate performance, low internal resistance and long cycle at the same time.

[0022] In particular, regarding the amount of the carbon-modified lithium metasilicate binder, the present invention strictly controls its content in the negative electrode active layer to 2.4% to 3.2%, so as to comprehensively regulate the strength of the cross-linked bonding network formed therein, and coordinate the mechanical properties, bonding properties and electrochemical properties of the obtained negative electrode active layer, so that when the obtained negative electrode active layer is used on the negative electrode plate of a lithium ion battery, the corresponding lithium ion battery exhibits more stable discharge performance.

[0023] In several preferred embodiments, the carbon-modified lithium metasilicate binder includes lithium metasilicate core particles and a carbon layer coated on the surface of the lithium metasilicate core particles, that is, the present invention realizes carbon modification by coating the carbon layer outside the lithium metasilicate material. Compared with other composite methods, this method of coating and forming a core-shell material can better exert the buffering property of carbon, and at the same time can better protect the hydroxyl groups on the surface of the lithium metasilicate particles, thereby more significantly improving the adhesion and conductivity of the resulting negative electrode active layer. And, in order to better balance the mechanical properties between the carbon layer and the lithium metasilicate core, improve the overall structural stability of the material, and ultimately optimize the cycle stability of the negative electrode active layer in which it is located, preferably the D50 of the lithium metasilicate core particles is 10nm ~ 120nm, and the thickness of the carbon layer is 0.1 nm ~ 10nm.

[0024] Furthermore, after a large number of experiments, the inventors have found that the surface hydroxyl density of the carbon-modified lithium metasilicate binder is preferably 0.02 g / cm 3 ~0.05g / cm 3 , and more preferably, the carbon-modified lithium metasilicate binder is subjected to thermogravimetric analysis, and the initial decomposition temperature of the carbon-modified lithium metasilicate binder is 300°C~800°C, and the weight loss percentage is 10%~20%. The carbon-modified lithium metasilicate binder with the above surface hydroxyl density can construct a cross-linked bonding network with a better structure in the negative electrode active layer where it is located, and while improving the bonding force, it can also promote Li + The effective transmission therein can comprehensively improve the bonding force and conductivity of the negative electrode active layer. In addition, compared with the lithium orthosilicate commonly used in the field as a component of the positive or negative electrode active layer, the lithium metasilicate used in the present invention, after being coated with the above carbon layer and obtaining the corresponding structure, shows higher thermal stability, thereby being able to more effectively improve the long-cycle stability of the negative electrode sheet and the lithium-ion battery in which it is located.

[0025] In several typical embodiments, the preparation method of the carbon-modified lithium metasilicate binder includes: step S1, pre-treating the lithium metasilicate powder to obtain lithium metasilicate core particles; step S2, mixing the lithium metasilicate powder with a carbon source under the protection of an inert gas, and calcining to obtain the carbon-modified lithium metasilicate binder. The inventors designed and optimized the preparation method of the carbon-modified lithium metasilicate binder through a large number of experiments and creative work, and obtained the above-mentioned process and conditions, thereby obtaining a carbon-modified lithium metasilicate binder with a more stable structure, a more suitable surface hydroxyl density, and higher thermal stability. It is used as a binder in the negative electrode active layer, and the resulting negative electrode active layer exhibits higher electrochemical performance and stability.

[0026] On the basis of the above process flow, the inventors have preferred the calcination temperature to be 400°C~1000°C and the time to be 0.2h~4.0h after a large number of experiments, so as to form a carbon layer with a more uniform and continuous coating and a better surface structure, optimize the overall material structure of the carbon-modified lithium metasilicate binder, make its internal stress lower and the expansion effect smaller, and more effectively protect the hydroxyl groups on the surface of the lithium metasilicate core particles to optimize its bonding force and improve the bonding and conductivity of the final negative electrode active layer. And, more preferably, the carbon source is selected from one or more of ethanol, ethylene, benzene, hexachlorobenzene and ethylene, because compared with the carbon sources such as citric acid, glucose and acetylene black commonly used in the preparation of coated materials in the art, the above carbon sources, especially the combination thereof, have higher reactivity and applicability, so when reacting with the coated material, a more uniform and stable carbon layer can be formed, and finally a carbon-modified lithium metasilicate binder with a more uniform, continuous and stable carbon layer is obtained, which effectively improves the stability of the negative electrode active layer in which it is located.

[0027] Further, in order to more effectively optimize the hydroxyl density on the surface of the obtained carbon-modified lithium metasilicate binder, preferably in step S1, the pretreatment includes: dissolving lithium metasilicate powder in a mixed solvent to obtain a mixed solution; drying the mixed solution at 40°C to 42°C to obtain lithium metasilicate core particles; preferably, the mixed solution includes tetraethyl orthosilicate, ethanol and water, and the weight ratio of tetraethyl orthosilicate, ethanol and water is 1: (1.8~2.0): 1; more preferably, the weight ratio of lithium metasilicate powder to the mixed solution is 1: (4.0~4.2). Pre-treating the lithium metasilicate powder in the above manner is not only conducive to the smooth progress of the subsequent carbon coating step, but also can comprehensively improve the structural stability of the obtained carbon-modified lithium metasilicate binder, and finally obtain a negative electrode active layer with better electrochemical performance. In particular, the inventors have optimized the mixed solvent used for pretreatment through a large number of experiments to be a mixed solvent with a weight ratio of 1: (1.8-2.0): 1 for tetraethyl orthosilicate, ethanol and water, and optimized the amount of the mixed solvent as above, because in the mixed solvent system, water can firstly act as a catalyst to promote the hydrolysis reaction of tetraethyl orthosilicate to generate silanol (Si-OH / Si(OH)4) and ethanol; at the same time, due to (Si-OH / Si(OH) 4 ), there are free hydroxyl groups in the mixed solvent system, so that some of the active hydroxyl groups existing on the surface of the lithium metasilicate powder can be better protected, and lithium metasilicate core particles with a more suitable surface hydroxyl density can be obtained, thereby more significantly improving the bonding and conductivity of the subsequent carbon-modified lithium metasilicate in the negative electrode active layer, and ultimately making the corresponding lithium-ion battery exhibit higher electrical performance and long cycle stability.

[0028] In several preferred embodiments, in order to further improve the electrical properties of the obtained negative electrode active layer and make the lithium ion battery in which it is located have a higher first effect and capacity, preferably, by weight percentage, the negative electrode active layer also includes 95.4% to 96.8% of the first negative electrode active material and 0.8% to 1.4% of the first conductive agent. And preferably, the first negative electrode active material is selected from one or more of graphite, silicon and lithium-containing alloys; the first conductive agent is selected from one or more of carbon black, carbon nanotubes and graphene. In theory, both the first negative electrode active material and the first conductive agent can be selected from the types commonly used in the art, as long as they can have the corresponding functions, but the inventors have selected the above-mentioned first negative electrode active materials and first conductive agents for the negative electrode active layer containing the carbon-modified lithium metasilicate binder provided by the present invention, and found that these types can better cooperate with the carbon-modified lithium metasilicate binder, prompting it to play a more outstanding role in improving adhesion and conductivity, and finally obtain a negative electrode active layer with excellent comprehensive performance.

[0029] The second aspect of the present invention provides a dual negative electrode active layer, comprising a first negative electrode active layer and a second negative electrode active layer stacked in sequence, the first negative electrode active layer is the above-mentioned negative electrode active layer, which includes a carbon-modified lithium metasilicate binder; in terms of weight percentage, the second negative electrode active layer includes 2.2%~3% of a CMC binder and / or an SBR binder, 95.5%~96.7% of a second negative electrode active material, and 0.7%~1.5% of a second conductive agent; the second negative electrode active material is selected from one or more of graphite, silicon, and a lithium-containing alloy; the second conductive agent is selected from one or more of carbon black, carbon nanotubes, and graphene.

[0030] On the basis of the above-mentioned negative electrode active layer, the present invention further uses it in combination with another negative electrode active layer with 2.2% to 3% CMC binder and / or SBR binder to obtain a double negative electrode active layer with a double-layer structure. The first negative electrode active layer including the carbon-modified lithium metasilicate binder has excellent adhesion, conductivity and intrinsic low dimensional expansion effect, and the second active layer can be used as a buffer layer to further improve the problem of damage to the active layer caused by poor elasticity of the lithium metasilicate core particles in the carbon-modified lithium metasilicate binder structure in the first negative electrode active layer. The two layers of negative electrode active layers work together to significantly improve the full charge rebound rate, cycle performance, rate performance and other issues of the lithium-ion battery cell in which they are located.

[0031] In a preferred embodiment, in the dual negative electrode active layer, the thickness ratio of the first negative electrode active layer to the second negative electrode active layer is (0.55~1.55):1. The inventor adjusted the thickness relationship between the first negative electrode active layer and the second negative electrode active layer through a large number of experiments, and optimized the ratio between the two to be within the above range, so that the mechanical properties of the two negative electrode active layers can be better matched, and a negative electrode active layer with higher structural stability and less prone to peeling and falling off, that is, better long-cycle stability, is obtained. In a more preferred embodiment, the second negative electrode active layer also includes 0.1%~0.3% of a carbon-modified lithium metasilicate binder by weight percentage. The inventors have found through a large number of experiments that further introducing the above-mentioned carbon-modified lithium metasilicate into the second negative electrode active layer at this mass fraction can enable a more significant synergistic effect to occur between the second negative electrode active layer and the first negative electrode active layer that already contains 2.4% to 3.2% of the carbon-modified lithium metasilicate binder, especially in terms of Li+ conduction. The two negative electrode active layers can cooperate better and have higher structural stability, thereby further improving the electrochemical performance of the resulting dual negative electrode active layer.

[0032] The third aspect of the present invention provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active layer disposed on at least one side of the surface of the negative electrode current collector, wherein the negative electrode active layer is the above-mentioned negative electrode active layer, or the above-mentioned double negative electrode active layer. Since the negative electrode active layer obtained by the present invention and the double negative electrode active layer including the negative electrode active layer have higher bonding force, better ion conductivity, and also retain excellent low dimensional expansion effect, after the negative electrode current collector is disposed thereon and the negative electrode sheet is obtained, the corresponding negative electrode sheet also exhibits higher electrical performance and long cycle stability.

[0033] Furthermore, it is preferred that the negative electrode active layer is the above-mentioned dual negative electrode active layer, so as to obtain a negative electrode plate with better electrical performance. In several typical embodiments, the first negative electrode active layer in the dual negative electrode active layer is arranged in contact with the negative electrode current collector; or, the second negative electrode active layer in the dual negative electrode active layer is arranged in contact with the negative electrode current collector. Among them, especially when the first negative electrode active layer is arranged in contact with the negative electrode current collector, because it has a higher ion conductivity than the second active layer, and can also serve as an intermediate layer between the negative electrode current collector and the second negative electrode active layer to play a more significant bonding role, when so arranged, the resulting negative electrode plate has more superior electrochemical properties, including electrical performance and cycle life.

[0034] A fourth aspect of the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet is the above-mentioned negative electrode sheet. Since the above-mentioned negative electrode sheet has higher adhesion, stability and electrical properties, the obtained lithium-ion battery exhibits higher rate performance and longer cycle life.

[0035] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0036] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0037] Example 1

[0038] 1. Preparation of carbon-modified lithium metasilicate binder:

[0039] Step (1), pretreatment: 60 g of lithium metasilicate powder with a D50 of 60 nm was dissolved in 240 g of a TEOS / ethanol / water (TEOS: ethanol: water = 1:2:1) mixed solvent to obtain a mixed solution, and the mixed solution was dried at 40°C, and then 60.2 g of lithium metasilicate with hydroxyl groups was separated, and the surface hydroxyl density was 0.042 g / cm 3 , that is, the lithium metasilicate core particles to be carbon-coated.

[0040] Step (2), introducing an inert gas into a reaction container, then heating the reaction container to 500° C., and adding the lithium metasilicate powder to be carbon-coated obtained in step (1);

[0041] Step (3), introducing 40% by volume of a mixed carbon source of ethanol, ethylene, benzene, hexachlorobenzene and ethylene into a reaction vessel to react with the lithium metasilicate powder to be carbon-coated for 2.5 hours to obtain a carbon-modified lithium metasilicate binder.

[0042] In the obtained carbon-modified lithium metasilicate binder, the D50 of the lithium metasilicate core particles is 60 nm, the thickness of the carbon layer is 4 nm, and the surface hydroxyl density of the carbon-modified lithium metasilicate binder is 0.03 g / cm 3 , thermogravimetric analysis showed that the initial decomposition temperature was 500°C and the weight loss percentage was 10%.

[0043] 2. Preparation of double negative electrode active layer:

[0044] The first negative electrode active layer: graphite is used as the negative electrode active material, carbon black is used as the conductive agent, and the above-obtained carbon-modified lithium metasilicate binder is used as the binder; the negative electrode active material is 96%, the conductive agent is 1.1%, and the binder is 2.9%.

[0045] The second negative electrode active layer: graphite is used as the negative electrode active material, carbon black is used as the conductive agent, and a mixture of CMC and SBR 1:1 is used as the binder; the negative electrode active material is 96.6%, the conductive agent is 1.2%, and the binder is 2.2%.

[0046] The thickness ratio of the first negative electrode active layer to the second negative electrode active layer is 1:1.

[0047] 3. Preparation of negative electrode sheet: The double negative electrode active layer obtained above is used as the negative electrode active layer, and the first negative electrode active layer is arranged in contact with the aluminum foil in the electrode sheet, that is, the negative electrode current collector.

[0048] Example 2

[0049] The only difference between this embodiment and embodiment 1 is that: in the preparation process of 1. carbon-modified lithium metasilicate binder, lithium metasilicate powder with D50 of 5 nm is selected for subsequent experiments, that is, in the obtained carbon-modified lithium metasilicate binder, the D50 of the lithium metasilicate core particles is 5 nm.

[0050] Example 3

[0051] The only difference between this embodiment and embodiment 1 is that: in the preparation process of 1. carbon-modified lithium metasilicate binder, lithium metasilicate powder with a D50 of 200 nm is selected for subsequent experiments, that is, in the obtained carbon-modified lithium metasilicate binder, the D50 of the lithium metasilicate core particles is 200 nm.

[0052] Example 4

[0053] The difference between this embodiment and embodiment 1 is that in the process of preparing the carbon-modified lithium metasilicate binder 1, the 240 g TEOS / ethanol / water (TEOS:ethanol:water=1:2:1) mixed solvent used in step (1) is changed to 200 g TEOS / ethanol (TEOS:ethanol=1:1) mixed solvent. The conditions of the other steps remain unchanged.

[0054] Example 5

[0055] The difference between this embodiment and embodiment 1 is that in the process of preparing the carbon-modified lithium metasilicate binder 1, the temperature of the drying treatment of the mixed solution in step (1) is changed from 40° C. to 60° C.

[0056] Example 6

[0057] The difference between this embodiment and embodiment 1 is that in the preparation process of 1. carbon-modified lithium metasilicate binder, only citric acid of equal mass is used as the carbon source.

[0058] Example 7

[0059] The difference between this embodiment and embodiment 1 is that in 2. the preparation process of the double negative electrode active layer, the amounts of the components in the two negative electrode active layers are different, specifically:

[0060] First negative electrode active layer: negative electrode active material 96.8%, conductive agent 0.8%, carbon-modified lithium metasilicate binder 2.4%.

[0061] Second negative electrode active layer: negative electrode active material 96.6%, conductive agent 1.2%, CMC+SBR binder 2.2%.

[0062] The thickness ratio of the first negative electrode active layer to the second negative electrode active layer is 0.55:1.

[0063] Example 8

[0064] The difference between this embodiment and embodiment 1 is that in 2. the preparation process of the double negative electrode active layer, the amounts of the components in the two negative electrode active layers are different, specifically:

[0065] First negative electrode active layer: negative electrode active material 95.4%, conductive agent 1.4%, carbon-modified lithium metasilicate binder 3.2%.

[0066] Second negative electrode active layer: negative electrode active material 95.5%, conductive agent 1.5%, CMC+SBR binder 3.0%.

[0067] The thickness ratio of the first negative electrode active layer to the second negative electrode active layer is 1.55:1.

[0068] Example 9

[0069] The difference between this embodiment and embodiment 1 is that in 2. the preparation process of the double negative electrode active layer, the amount of each component in the first negative electrode active layer is different, specifically:

[0070] First negative electrode active layer: negative electrode active material 95%, conductive agent 2.1%, carbon-modified lithium metasilicate binder 2.9%.

[0071] At the same time, the thickness ratio of the first negative electrode active layer to the second negative electrode active layer is set to 0.5:1.

[0072] Example 10

[0073] The difference between this embodiment and embodiment 1 is that in 2. the preparation process of the double negative electrode active layer, the amount of each component in the first negative electrode active layer is different, specifically:

[0074] First negative electrode active layer: negative electrode active material 97%, conductive agent 0.1%, carbon-modified lithium metasilicate binder 2.9%.

[0075] At the same time, the thickness ratio of the first negative electrode active layer to the second negative electrode active layer is set to 2:1.

[0076] Embodiment 11

[0077] The only difference between this embodiment and embodiment 1 is that the second negative electrode active layer is not prepared, that is, only the first negative electrode active layer is used as the negative electrode active layer for the negative electrode plate.

[0078] Example 12

[0079] The difference between this embodiment and embodiment 1 is that: in 3. the preparation process of the negative electrode plate, the double negative electrode active layer is used as the negative electrode active layer, and the second negative electrode active layer is arranged in contact with the aluminum foil in the plate, that is, the negative electrode current collector.

[0080] Example 13

[0081] The only difference between this embodiment and embodiment 1 is that in 2. the preparation process of the dual negative electrode active layer, the binder in the second negative electrode active layer includes 1.0% CMC, 1.0% SBR and 0.2% of the carbon-modified lithium metasilicate binder obtained in step 1.

[0082] Comparative Example 1

[0083] The difference between this comparative example and Example 1 is that in 2. the preparation process of the double negative electrode active layer, the amounts of the components in the first negative electrode active layer are different, specifically:

[0084] First negative electrode active layer: negative electrode active material 96.8%, conductive agent 1.2%, carbon-modified lithium metasilicate binder 2.0%.

[0085] Comparative Example 2

[0086] The difference between this comparative example and Example 1 is that in 2. the preparation process of the double negative electrode active layer, the amounts of the components in the first negative electrode active layer are different, specifically:

[0087] First negative electrode active layer: negative electrode active material 95.4%, conductive agent 1.0%, carbon-modified lithium metasilicate binder 3.6%.

[0088] Comparative Example 3

[0089] The difference between this comparative example and Example 1 is that: in the process of preparing the carbon-modified lithium metasilicate binder, the lithium metasilicate powder to be coated with carbon obtained in step (1) is directly used as a binder to prepare a dual negative electrode active layer, and then obtain a negative electrode plate.

[0090] Comparative Example 4

[0091] The difference between this comparative example and Example 1 is that: in the preparation process of 1. carbon-modified lithium metasilicate binder, an equal weight of lithium orthosilicate powder is used to replace lithium metasilicate powder to obtain carbon-modified lithium orthosilicate powder and use it as a binder to prepare a dual negative electrode active layer, and then obtain a negative electrode plate.

[0092] Comparative Example 5

[0093] The difference between this comparative example and Example 1 is that the first negative electrode active layer is not prepared, that is, only the second negative electrode active layer is used as the negative electrode active layer for the negative electrode plate. That is, the negative electrode active layer of the obtained negative electrode plate has only one layer, and does not contain the carbon-modified lithium metasilicate binder, but only contains CMC and SBR binders.

[0094] Test Method

[0095] Energy efficiency is measured using a square cell environmental chamber instrument, with the following steps: 1. Adjust to 25±2℃; 2. Rest for 30min; 3. 0.5P CP to 3.65V to obtain charging energy; 4. Rest for 10min; 5. 0.5P DP to 2.5V to obtain discharging energy; 6. Rest for 10min; 7. Repeat step 2-6 for 4 cycles. The energy efficiency of the second-to-last cycle is taken as the first efficiency.

[0096] Internal resistance test is carried out using an ohmmeter.

[0097] The cycle test is carried out using a square battery cell environmental chamber instrument, with the following steps: 1. Adjust to 25±2℃; 2. Rest10min; 3. 0.5P CP to 3.65V; 4. Rest 10min; 5. 0.5P DP to 2.5V; 6. Rest 10min; 7. Cycle steps 3-6 for a total of 100 cycles, and calculate the capacity retention rate.

[0098] The negative electrode sheets obtained in the above-mentioned embodiments and comparative examples were prepared into lithium-ion battery samples, and were tested as above. The results are shown in Table 1.

[0099] Table 1

[0100]

[0101] From the above description, it can be seen that the above-mentioned embodiment of the present invention realizes the preparation of a lithium-ion battery negative electrode active layer containing carbon-modified lithium metasilicate, which can improve the internal resistance, adhesion and ion conductivity of the negative electrode plate, and ultimately obtain a lithium-ion battery that can take into account high rate performance, low internal resistance and long cycle.

[0102] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A negative electrode active layer, characterized in that: The negative electrode active layer includes a carbon-modified lithium metasilicate binder, and the content of the carbon-modified lithium metasilicate binder is 2.4% to 3.2% based on the total weight of the negative electrode active layer as 100%; The preparation method of the carbon-modified lithium metasilicate binder comprises: Step S1, dissolving lithium metasilicate powder in a mixed solvent to obtain a mixed solution; drying the mixed solution at 40° C. to 42° C. to obtain lithium metasilicate core particles; The mixed solvent includes tetraethyl orthosilicate, ethanol and water, and the weight ratio of the tetraethyl orthosilicate, the ethanol and the water is 1: (1.8-2.0): 1; Step S2, under the protection of an inert gas, mixing the lithium metasilicate core particles with a carbon source, and calcining to obtain the carbon-modified lithium metasilicate binder; The carbon-modified lithium metasilicate binder comprises the lithium metasilicate core particles and a carbon layer coated on the surface of the lithium metasilicate core particles.

2. The negative electrode active layer according to claim 1, characterized in that The D50 of the lithium metasilicate core particles is 10 nm to 120 nm, and the thickness of the carbon layer is 0.1 nm to 10 nm.

3. The negative electrode active layer according to claim 2, characterized in that: Thermogravimetric analysis of the carbon-modified lithium metasilicate binder shows that the initial decomposition temperature of the carbon-modified lithium metasilicate binder is 300° C. to 800° C., and the weight loss percentage is 10% to 20%.

4. The negative electrode active layer according to claim 1, characterized in that: In terms of weight percentage, the negative electrode active layer further comprises 95.4% to 96.8% of the first negative electrode active material and 0.8% to 1.4% of the first conductive agent; And / or, the first negative electrode active material is selected from one or more of graphite, silicon and lithium-containing alloy; the first conductive agent is selected from one or more of carbon black, carbon nanotubes and graphene.

5. A double negative electrode active layer, comprising a first negative electrode active layer and a second negative electrode active layer stacked in sequence, characterized in that: The first negative electrode active layer is the negative electrode active layer according to any one of claims 1 to 4, comprising a carbon-modified lithium metasilicate binder; In terms of weight percentage, the second negative electrode active layer includes 2.2% to 3% of a CMC binder and / or an SBR binder, 95.5% to 96.7% of a second negative electrode active material, and 0.7% to 1.5% of a second conductive agent; The second negative electrode active material is selected from one or more of graphite, silicon and lithium-containing alloy; The second conductive agent is selected from one or more of carbon black, carbon nanotubes and graphene.

6. The double negative electrode active layer according to claim 5, characterized in that: In the double negative electrode active layer, the thickness ratio of the first negative electrode active layer to the second negative electrode active layer is (0.55-1.55):1; And / or, by weight percentage, the second negative electrode active layer further includes 0.1% to 0.3% of the carbon-modified lithium metasilicate binder.

7. A negative electrode sheet, comprising a negative electrode current collector and a negative electrode active layer disposed on at least one side surface of the negative electrode current collector, characterized in that: The negative electrode active layer is the negative electrode active layer according to any one of claims 1 to 4, or the double negative electrode active layer according to claim 5 or 6.

8. The negative electrode sheet according to claim 7, characterized in that: The negative electrode active layer is the double negative electrode active layer, and The first negative electrode active layer in the double negative electrode active layer is arranged in contact with the negative electrode current collector; or, The second negative electrode active layer in the double negative electrode active layer is arranged in contact with the negative electrode current collector.

9. A lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, characterized in that: The negative electrode plate is the negative electrode plate according to claim 7 or 8.

Citation Information

Patent Citations

  • Negative pole piece as well as preparation method and application thereof

    CN114927643A

  • Negative-electrode material for nonaqueous - electrolyte secondary battery production process for the same, negative electrode for nonaqueous-electrolyte secondary battery, and nonaqueous-electrolyte secondary battery

    US20150188127A1